Challenges Faced by Students of Secretary Program in Speaking English:: A Case Study of ASM Santa Maria Semarang - Fitria Wahyu Nugraheni (Regalia Institute, 2023)
Nowadays, English has become a global language used in various fields including business, technology, and communication, hence it makes English even more important to learn in order to communicate with people of different languages and cultural backgrounds. In Indonesia, many students still cannot speak English fluently since the students studied too many subject skills. In addition, teaching emphasized on grammar rule rather than communicative English. This current research focuses in challenges faced by students of Secretary Program in Speaking English since based on the observation of researcher that students feel difficult in practicing speaking, whereas having good speaking skill is a must for students in Secretary Program to support their job in the future. The objectives of this research are: (1) to find out the problems of speaking faced by students and, (2) to find out the cause of difficulties. After doing this current research, it is expected to solve the problems in speaking skills for secretary program in ASM Santa Maria Semarang. The subjects of this research were students from second and fourth semester of ASM Santa Maria Semarang. The open-ended questionnaire and semi-structured interviews were used to collect the data. The findings revealed that learners typically experience four main speaking obstacles: personal problem, social problem, linguistic problem, and environmental problem. Moreover, the researcher classified causes into four majors: teacher and teaching factors, mother tongue factor, course content factor, and classroom culture. In order to give students of Secretary program, the lecturer can create speaking practice; including practice in handling telephone, role play to make students’ conversation fluently, and practice in presenting a project. Besides, the lecturer is also encouraging group discussions among students and holding speaking events like public speaking competitions and debates. Keywords: Difficulties, Secretary Program, Speaking